2018
DOI: 10.1021/acsaem.8b00602
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Planar Perovskite Solar Cell Performance via Contact Passivation of TiO2/Perovskite Interface with NaCl Doping Approach

Abstract: Perovskite solar cells (PSCs) have been developed rapidly in recent years due to the excellent photoelectric properties and development potential. In this study, high performance and hysteresis-less planar structured perovskite (MA 1−y FA y PbI 3−x Cl x ) solar cell was successfully achieved via contact passivation of the compact titanium dioxide (TiO 2 )/ perovskite interface with NaCl doping method. It was found that the sodium chloride (NaCl) doping treatment on TiO 2 could significantly improve the electri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
48
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 72 publications
(51 citation statements)
references
References 44 publications
3
48
0
Order By: Relevance
“…The optimized lattice constants of a = b = 4.737 Å and c = 3.185 Å for SnO 2 , and a = b = 8.715 Å and c = 12.835 Å for tetragonal CH 3 NH 3 PbI 3 which are in good agreement with previous reports . To minimize the mismatch between CH 3 NH 3 PbI 3 surface and SnO 2 surface, the CH 3 NH 3 PbI 3 /SnO 2 interfaces, as shown in Figure , were constructed by 1 × 1 supercell CH 3 NH 3 PbI 3 (110), and 2 × 4 supercell SnO 2 (110) surfaces according to previous experimental and theoretical results . The mismatches between CH 3 NH 3 PbI 3 and SnO 2 supercell surfaces were less than 4.29%, as listed in Table 1 .…”
Section: Resultssupporting
confidence: 83%
“…The optimized lattice constants of a = b = 4.737 Å and c = 3.185 Å for SnO 2 , and a = b = 8.715 Å and c = 12.835 Å for tetragonal CH 3 NH 3 PbI 3 which are in good agreement with previous reports . To minimize the mismatch between CH 3 NH 3 PbI 3 surface and SnO 2 surface, the CH 3 NH 3 PbI 3 /SnO 2 interfaces, as shown in Figure , were constructed by 1 × 1 supercell CH 3 NH 3 PbI 3 (110), and 2 × 4 supercell SnO 2 (110) surfaces according to previous experimental and theoretical results . The mismatches between CH 3 NH 3 PbI 3 and SnO 2 supercell surfaces were less than 4.29%, as listed in Table 1 .…”
Section: Resultssupporting
confidence: 83%
“…However, different groups demonstrated the potentiality of introducing alkali cation at the perovskite interfaces. For instance, alkali metal halides were successfully implemented at the ESL|PSK interface in n‐i‐p architecture . It was also demonstrated that NaCl can ameliorate the morphology of single‐step deposited CH 3 NH 3 PbI 3 , however we do not observe any sizeable variation in the morphology and in the crystallinity of the perovskite layer (Figures S8 and S17, Supporting Information).…”
Section: Resultsmentioning
confidence: 77%
“…The average lifetimes derived from the fitting curves were around 25.7 and 29.8 ns for perovskite films with and without TiCl 4 treatment, respectively. The decreased PL lifetime is related to the efficient charge carrier transfer induced quenching process [27]. This is essential for efficient charge extraction and collection of the device.…”
Section: Resultsmentioning
confidence: 99%
“…Hence, various interface transporting layers have been studied. Among them, metal oxides (e.g., ZnO, SnO 2 , and TiO 2 ) have been widely investigated as electron-transporting layers (ETLs) in PSCs [23][24][25][26][27][28][29][30][31][32][33][34][35][36][37], particularly TiO 2 ETL. The surface and electronic properties of TiO 2 play important roles in determining the final device performance, including power conversion efficiency (PCE), hysteresis behavior, and stability [20,38,39].…”
Section: Introductionmentioning
confidence: 99%